2018
DOI: 10.1016/j.pmedr.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of food insecurity among food bank users in Germany and its association with population characteristics

Abstract: The prevalence of food insecurity (FI) among food bank users in many European countries is unknown. The study aims to examine FI prevalence and associated population characteristics among this particular group of disadvantaged people in Germany. Food insecurity status was assessed among 1033 adult food bank users with a mean age of 53 years (57% female, 43% male) in Germany in 2015 using the food insecurity experience scale (FIES). About half of the participants (55.8%) were single with no children and born in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 42 publications
3
39
2
3
Order By: Relevance
“…Smith, Rabbitt and Coleman-Jensen, 2017) it is found that the most vulnerable people to food insecurity usually have the low level of education and they are unemployed. Consistent with the findings of studies carried out in other countries, our study found that female-headed households are more likely to be food insecure than a man-headed household (Magaña-Lemus et al, 2016;Martin-Fernandez et al, 2013) and food insecurity is positively correlated with poor self-reported health (Alvarez et al, 2015;Depa et al, 2018). Our results also confirm the inverted U-shape relationship between the age of the HH and the prevalence of FI found for middle-income and high-income economies in the literature (Smith, Rabbitt and Coleman-Jensen, 2017).…”
Section: Source: Own Evaluationsupporting
confidence: 92%
See 1 more Smart Citation
“…Smith, Rabbitt and Coleman-Jensen, 2017) it is found that the most vulnerable people to food insecurity usually have the low level of education and they are unemployed. Consistent with the findings of studies carried out in other countries, our study found that female-headed households are more likely to be food insecure than a man-headed household (Magaña-Lemus et al, 2016;Martin-Fernandez et al, 2013) and food insecurity is positively correlated with poor self-reported health (Alvarez et al, 2015;Depa et al, 2018). Our results also confirm the inverted U-shape relationship between the age of the HH and the prevalence of FI found for middle-income and high-income economies in the literature (Smith, Rabbitt and Coleman-Jensen, 2017).…”
Section: Source: Own Evaluationsupporting
confidence: 92%
“…In-depth examination of the food insecurity profile in these countries can be an interesting issue for readers not only from the V4 but also for researchers outside of these countries. First of all, up to now microeconometric analyses of food insecurity in the EU have focused mainly on the situation in Western European countries, such as France (Martin-Fernandez et al, 2013) or Germany (Depa et al, 2018). Instead, this paper sheds a light on the situation of households in Central European countries, filling to some extent the gap in this regard.…”
Section: Introductionmentioning
confidence: 97%
“…The FIES also serves as one of two indicators chosen to monitor Target 2.1 of the United Nations’ 2030 Agenda for Sustainable Development (Target 2.1 aims to end hunger and ensure access by all people, in particular the poor and those in vulnerable situations, including infants, to safe, nutritious and sufficient food all year round, by 2030) [ 16 , 17 ]. The FIES is a relatively new approach in measuring FI, but has been used numerous times for assessing FI in the global context [ 15 , 18 , 19 ] and in selected countries or regions [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most research on FI in Europe is focused mainly on the situation in Western European countries, such as the United Kingdom [ 23 ], Ireland [ 24 ], and Germany [ 20 ]. This paper sheds a light on the situation of households in Poland, a central European middle-income country.…”
Section: Introductionmentioning
confidence: 99%
“…Por se tratar de um grupo com fortes carências alimentares que condicionam o seu bem-estar físico e psicológico, geralmente, a vulnerabilidade é caracterizada como extrema (Loopstra e Lalor, 2017). Depa, Gyngell, Muller, Eleraky, Hilzendegen e Stroebele-Benschop (2018) caracterizam os beneficiários de IAA´s não só como pertencentes a um grupo vulnerável, mas também a uma "população socialmente desfavorecida", reforçando assim a ligação entre vulnerabilidade e desigualdade social, previamente enunciada por Silva (1995).…”
Section: Da Sensibilidade à Vulnerabilidade: Os Contornos Dos Conceitosunclassified